Nicht alle fliegen - die Alternative Nachtzug. Nachfragedeterminanten im europäischen Markt für Nachtreiseverkehre. - Schlaak, Jan-Philipp; Hödl, Sonja (Deutscher Verkehrs-Verl., 2007)
Die Anfänge des Nachtreisezugverkehrs reichen bis in die Mitte des 19. Jahrhunderts zurück. War eine Nachtzugreise, die häufig weit länger dauerte als die Nacht, noch bis in die Mitte des 20. Jahrhunderts für den überwiegenden Teil der Reisenden die einzige wirtschaftliche Möglichkeit zur Raumüberwindung langer Distanzen auf den Kontinenten, begann sich dies durch die Etablierung von Substituten zunehmend zu ändern. difu

In the long haul travel sector, overnight trains have enjoyed a role rich in tradition yet their importance vis-à-vis other means of transport has diminished significantly. The question is how this sector will develop in future - taking into account the advantage of rail travel as such - in line with market requirements in order to face the competitive services offered by other modes of transport. The report highlights interesting achievements in the overnight train segment and also examines demand determinants with a view to improving the services on offer and strengthening competitive standing. The results of a survey undertaken on board of overnight trains have been taken into account. difu
Keywords: Verkehr; Eisenbahn; Schienenpersonenverkehr; Befragung; Reisezeit; Tageszeit